METHODOLOGY OF ORGANIZING AND DEVELOPING THE EDUCATIONAL PROCESS ON THE BASIS OF DIGITAL TECHNOLOGIES IN EDUCATIONAL CLUSTER CONDITIONS - Fayzullayeva, Madina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
In this article, several methods of organizing and developing the educational process on the basis of digital technologies in educational cluster conditions have been developed. These methods were created based on the experiences and conclusions of Z.K.Bekturiva and N.N.Vagapova.